Probiotic Pediococcus pentosaceus ameliorates MPTP-induced oxidative stress via regulating the gut microbiota–gut–brain axis - Pan, Sipei; Wei, Hongming; Yuan, Shushu; Kong, Yu; Yang, Huiqun; Zhang, Yuhe; Cui, Xiaorui; Chen, Weian; Liu, Jiaming; Zhang, Yang (Frontiers in Cellular and Infection Microbiology, 2022)
Recent evidence demonstrated that functional bacteria were involved in the regulation of Parkinson’s disease (PD). However, the mechanism of probiotics in improving PD was unclear. Here, the antioxidant effect and its mechanism of probiotics Pediococcus pentosaceus (PP) on PD were studied by regulating gut-brain axis. In this study, male C57BL/6J mice were injected MPTP intraperitoneally to establish PD model, and then were treated with PP for 4 weeks. Subsequently, a series of neurobehavioral tests to evaluate the motor function of mice were performed. Additionally, degeneration of dopaminergic neurons, accumulation of α-synuclein, the production of oxidative stress response and the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) pathway related proteins were evaluated. Moreover, gut microbial composition and the level of metabolite γ-aminobutyric acid (GABA) were assessed. The results showed that PP treatment could improve MPTP-induced motor deficits, degeneration of dopaminergic neurons and accumulation of α-synuclein. Moreover, PP treatment significantly increased the levels of SOD1, Gpx1 and Nrf2, while decreased the levels of Keap1 in the brain of MPTP-induced mice. Notably, PP treatment improved gut microbial dysbiosis and increased the level of GABA in MPTP-induced mice. These findings indicated that PP might represent a promising candidate due to the metabolite of GABA, that could be used for treatment of PD.